Advances in Microfluidic Technologies for Energy Storage and Release Systems. Issue 10 (11th August 2022) - Cheng, Samuel Kok Suen; Li, Tong; Meena, Stephene Shadrack; Cao, Qianan; Li, Binglin; Kosgei, Benson Kiprono; Cheng, Tingjun; Luo, Ping; Liu, Qingjun; Zhu, Genhua; Liu, Qian; Han, Ray P.S.
Abstract : While the majority of the technologies developed for energy storage are macrosized, the reactions involved in energy storage, such as diffusion, ionic transport, and surface‐based reactions, occur on the microscale. In light of this, microfluidics with the ability to manipulate such reactions and fluids on the micrometer scale has emerged as an interesting platform for the development of energy storage systems. Herein, the advances in utilizing microfluidic technologies in energy storage and release systems are reviewed in terms of four aspects. First, miniaturized microfluidic devices to store various forms of energy such as electrochemical, biochemical, and solar energy with unique architectures and enhanced performances are discussed. Second, novel energy materials with the desired geometries and characteristics that can be fabricated via microfluidic techniques are reviewed. Third, applications enabled by such microfluidic energy storage and release systems, particularly focusing on medical, environmental, and modeling purposes, are presented. Lastly, some remaining problems and challenges and possible future works in this field are suggested. Abstract : The current status and developments of microfluidic technologies in energy storage and release are systematically reviewed. Emphases are placed in microfluidic energy storing devices, energy materials fabricated by microfluidic techniques, and the applications of microfluidic energy storage and release systems. Furthermore, the potential directions for future works are proposed.